Prolongation of rat corneal graft survival by treatment with anti-CD4 monoclonal antibody. Issue 10 (October 1992) - Ayliffe, W; Alam, Y; Bell, E B; McLeod, D; Hutchinson, I V
Abstract : A rat model of orthotopic corneal graft rejection was used to investigate the effect of depletion of subpopulations of immune cells by treatment with monoclonal antibodies. Though CD4+ cells were not eliminated completely by anti-CD4 monoclonal antibodies there was a profound delay in the rejection times of orthotopic corneal allografts. Furthermore a third of the CD4+ depleted animals failed to reject corneal allografts by 100 days post grafting. Despite an almost complete depletion of circulating CD8+ cells, the anti-CD8 antibody treated animals rejected corneal allografts in a similar time course to allografted controls treated with a non-reactive control antibody OX21. These results demonstrate that CD8+ T-cells are not required for rejection of corneal allografts whereas CD4+ T-cells play a critical role in the rejection response. Treatment with anti-CD4 antibodies may have a useful clinical application.